Political Education: Objectives, Mechanisms and Method Requirements - Roghayeh Barzegar; Mohammadhasan Karimi; Khalil-allah Sardarnia; Mohammad Mazidi (رهیافتهای سیاسی و بین المللی)
In today's world, political and civic education is a part of the process of political development and the most important mechanism for citizenship, which plays a key role in establishing national sovereignty and unity. The purpose of this study is to investigate the essence of political education, goals, and ultimately to find the mechanism and method of appropriate political education in Iran. The following paper seeks to answer these two main questions: 1. What is Political Education? 2. What are the goals, mechanisms and requirements for the method of political education in Iran? The paradigm of this research is qualitative. So in order to answer the first question in the framework of a phenomenological approach, by reviewing different perspectives, a general concept of political education is presented and then, in response to the second question, the method of analytic logic or transcendental analysis has been used. Findings of the research indicate that political education is a process by which the legitimacy of sovereignty, lawmaking, discourse, the improvement of life and human flourishing will be done. This requires the creation of democracy, the discourse and the public sphere, by providing individual conditions (1. familiarity with the method of reasoning or logic; 2. familiarity with legal literacy or constitution and citizenship rights) and social conditions (1. freedom of expression and belief; 2. A place to exchange views) in the shadow of education.